A Comprehensive Case Study on Traditional Weaving of Western Rajasthan - Srivastava, Ankita; Saxena, Ankur (Journal of Business Management and Accounting, 2024)
The present paper discusses an age-old craft practised in India named Pattu weaving. This weaving technique is based on the extra weft weave design. Along with the ground warp and weft, few extra bright colored yarns are used in this technique to weave beautiful motifs on the fabric during the weaving process. The craft follows the sustainable way of fabric manufacturing as the fabrics are made on the handloom and follow the traditional ways for pre-weaving process also. The craft becomes more relevant in the present scenario considering the fact that for the last few decades unsustainable practices have increased drastically due to the imbalance of demand and supply, scarcity of natural resources, advent of unsustainable technologies among the other factors. While traditionally, sustainable practices were an integral part of the lifestyle of human beings and balanced the eco-system of the earth. One of the ways for balancing the natural energy consumption is utilization of all natural resources wisely by reinventing traditional craft practices. Hence, the present study focuses on the materials, tools, techniques and processes used in the Pattu weaving craft. PASTLE analysis of the craft has also been done to understand the opportunity and challenges of the craft. Along with this, a comparative analysis of the traditional and contemporary raw materials, techniques, motifs, colour range and application of the craft have also been covered in this paper. For this study, the primary research is based on the information that was collected during Craft Research Documentation activity funded by the Ministry of Textiles, India. Data from Secondary research has also been added to strengthen the analysis.
Keywords: Sustainable manufacturing; craft; weaving; extra weft technique; geometrical motifs